1978
DOI: 10.1021/jm00202a018
|View full text |Cite
|
Sign up to set email alerts
|

Studies in the (+)-morphinan series. 5. Synthesis and biological properties of (+)-naloxone

Abstract: (+)-Naloxone was prepared in 26% overall yield in eight steps from (+)-7-bromodihydrocodeinone dimethyl ketal by a synthesis which excluded enantiomeric contamination. (+)-Naloxone was examined in three assay systems and found to have no more than 1/1000(-1)/10 000th the activity of (-)-naloxone; it can, thus, serve to test the stereospecificity of the biochemical and pharmacological actions of (-)-naloxone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(89 citation statements)
references
References 5 publications
4
85
0
Order By: Relevance
“…Interestingly, studies in the Parkinson's disease model, in particular, have shown that both NAL stereoisomers are equally neuroprotective Liu et al, 2002). In contrast, only (−)-naloxone isomer binds to and antagonizes opioid receptors, while the (+)-enantiomer is inert in this regard (Iijima et al, 1978;Marcoli et al, 1989). Further investigations have now fully dissociated the neuroprotective effect of NAL from its opioid receptor signaling (Liu and Hong, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, studies in the Parkinson's disease model, in particular, have shown that both NAL stereoisomers are equally neuroprotective Liu et al, 2002). In contrast, only (−)-naloxone isomer binds to and antagonizes opioid receptors, while the (+)-enantiomer is inert in this regard (Iijima et al, 1978;Marcoli et al, 1989). Further investigations have now fully dissociated the neuroprotective effect of NAL from its opioid receptor signaling (Liu and Hong, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This receptor is therefore tentatively defined as the naloxonesensitive sigma receptor, which resembles the opiate sigma receptor originally proposed by Martin et al (1976). (+)-Naloxone, an enantiomer of the non-selective µ-opioid receptor antagonist naloxone, has been shown not to have any affinity for µ-opioid receptors or block µ-opioid mediated analgesia (Iijima et al, 1978b). (+)-Naloxone and the sigma receptor antagonist BD1047 were then used as the receptor antagonist to determine if the antianalgesia induced by (+)-morphine or (−)-morphine is mediated by the activation of the naloxonesensitive sigma receptors.…”
Section: Pretreatment With (+)-Morphine or (−)-Morphine Attenuates Thmentioning
confidence: 99%
“…This distinction between the effect of (1)-naloxone on locomotor activity induced by heroin/6-AM and morphine may suggest that heroin/6-AM involves non-ORs/targets such as TLR4 in a different manner than morphine. However, a more likely explanation is a nonspecific effect of high doses of (1)-naloxone on ORs, since high concentrations of (1)-naloxone/naltrexone will also antagonize ORs, although with approximately 2500-10,000 times lower binding affinities (Iijima et al, 1978;Theberge et al, 2013). By extrapolating from Table 2, we can calculate that brain concentrations after 50 mg/kg (1)-naloxone were approximately 3500-5000 times higher than after 0.01 mg/kg (2)-naloxone, indicating possible OR antagonism.…”
Section: Discussionmentioning
confidence: 99%
“…(1)-Naloxone hydrochloride was synthesized (Iijima et al, 1978) by Dr. Kenner C. Rice (National Institute on Drug Abuse and National Institute on Alcohol Abuse and Alcoholism, National Institutes of Health, Bethesda, MD). The commercial suppliers reported purities .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation